Prognostic Role of Pretreatment De Ritis Ratio (Aspartate Transaminase/Alanine Transaminase Ratio) in Urological Cancers: A Systematic Review and Meta-Analysis - Su, Shiqiang; Liu, Lizhe; Li, Chao; Zhang, Jin; Li, Shen (Frontiers in Oncology, 2020)
Background: To examine the potential prognostic significance of pretreatment De Ritis ratio (aspartate transaminase/alanine transaminase ratio) in urological cancers, including upper tract urothelial cancer (UTUC), renal cell carcinoma (RCC), prostate cancer (PCa), bladder cancer (BCa). Methods: Potential literatures were searched with PubMed, Embase, Cochrane Library, and Web of Science in December 2019. Merged hazard ratios (HRs) and 95% confidence intervals (CIs) were used to evaluate the associations. Results: Totally, 15 studies with 8,565 patients were included. Merged results showed that an elevated pretreatment De Ritis ratio was correlated with poorer OS (HR 1.80, 95% CI 1.61–2.01), CSS (HR 2.15, 95% CI 1.80–2.56), PFS (HR 1.57, 95% CI 1.34–1.85), BRFS (HR 1.67, 95% CI 1.11–2.53) for urological cancers. Subgroup analyses by cancer type for OS found that De Ritis ratio can be a predictor in UTUC (HR 1.91, 95% CI 1.57–2.33), RCC (HR 1.74, 95% CI 1.47–2.07), and BCa (HR 1.80, 95% CI 1.43–2.27). Similar results could be found for CSS (UTUC: HR 2.46, 95% CI 1.93–3.13; RCC: HR 1.90, 95% CI 1.46-2.47; BCa: HR 2.71, 95% CI 1.39-5.31) and PFS (UTUC: HR 1.59, 95% CI 1.15–2.20; RCC: HR 1.52, 95% CI 1.26–1.83; BCa: HR 1.79, 95% CI 1.18–2.72). There was no publication bias among these included studies. Conclusions: Pretreatment De Ritis ratio was a significant predictor for OS, CSS, PFS and BRFS in urological cancers, indicating that it could be a promising prognostic factor during clinical practice.